2021
DOI: 10.1016/s0140-6736(21)00432-3
|View full text |Cite|
|
Sign up to set email alerts
|

Single-dose administration and the influence of the timing of the booster dose on immunogenicity and efficacy of ChAdOx1 nCoV-19 (AZD1222) vaccine: a pooled analysis of four randomised trials

Abstract: Background The ChAdOx1 nCoV-19 (AZD1222) vaccine has been approved for emergency use by the UK regulatory authority, Medicines and Healthcare products Regulatory Agency, with a regimen of two standard doses given with an interval of 4–12 weeks. The planned roll-out in the UK will involve vaccinating people in high-risk categories with their first dose immediately, and delivering the second dose 12 weeks later. Here, we provide both a further prespecified pooled analysis of trials of ChAdOx1 nCoV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
971
7
20

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,045 publications
(1,082 citation statements)
references
References 8 publications
49
971
7
20
Order By: Relevance
“…Single dose vaccine efficacy >22 days post-first dose has been reported as 69-76%. 14,15 No real-world data on vaccine effectiveness against PCR-positive infections has been published, but preliminary analyses show a reduction in hospital admissions in Scotland. 16 A novel SARS-CoV-2 variant, B.1.1.7, identified in September-2020 in the UK, has spread rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Single dose vaccine efficacy >22 days post-first dose has been reported as 69-76%. 14,15 No real-world data on vaccine effectiveness against PCR-positive infections has been published, but preliminary analyses show a reduction in hospital admissions in Scotland. 16 A novel SARS-CoV-2 variant, B.1.1.7, identified in September-2020 in the UK, has spread rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…A common concern about implementing the deferred second dose strategy is that the one dose efficacy duration is unknown for now. AstraZeneca’s one dose trial data showed sustained one dose immunity for at least 12 weeks (13), but given that it did not use the novel mRNA vaccine technology, the concern around one dose duration was still valid. However, with multiple ongoing studies evaluating one dose efficacy duration of the mRNA vaccines (such as in Quebec and the UK), this risk has greatly been diminished.…”
Section: Resultsmentioning
confidence: 99%
“…A three month interval between doses of the Oxford-AstraZeneca vaccine results in higher vaccine efficacy (81%) than only a six week interval (55%), and the first dose offers 76% protection from 22 days onwards, showed the results of post-hoc exploratory analyses from a phase III randomised controlled trial published in the Lancet 1. The study, which was published as a preprint at the start of February,2 also confirmed vaccine efficacy against symptomatic disease after two doses, with no hospital admissions or deaths among the people vaccinated (8597 participants), compared with 15 instances in the control group (8581).…”
Section: Vaccinesmentioning
confidence: 99%